Distributed Optimal Control of Energy Storages in a DC Microgrid With Communication Delay - Shi, Mengxuan; Chen, Xia; Zhou, Jianyu; Chen, Yin; Wen, Jinyu; He, Haibo (IEEE transactions on smart grid, 2020)
For a distributed DC microgrid, the conventional voltage control highly relies on the accuracy of the voltage observer, and the observer will produce an estimation error under time delays. To address the problem brought by the voltage observer, this paper transforms the voltage control into an optimization problem and integrates it into the power sharing control based on the PI consensus algorithm. With the proposed optimal control, the DC bus voltage control and proportional power sharing of the energy storages can be realized in one controller, so that the controller structure is dramatically simplified and the control accuracy will not be affected by the time delay. In addition, to further improve the system stability to resist delay, scattering transformation is introduced in the distributed optimal controller. By constructing Lyapunov function, it has been proved that the stability of the controller under the time delay can be guaranteed. Simulations are conducted to verify the effectiveness of the proposed control strategy and the transformation with and without time delay.